Archaeal lipids in oral delivery of therapeutic peptides - Jacobsen, Ann-Christin; Fricker, Gert (European journal of pharmaceutical sciences, 2017)
Archaea contain membrane lipids that differ from those found in the other domains of life (Eukarya and Bacteria). These lipids consist of isoprenoid chains attached via ether bonds to the glycerol carbons at the sn-2,3 positions. Two types of ether lipids are known, polar diether lipids and bipolar tetraether lipids. The inherent chemical stability and unique membrane-spanning characteristics of tetraether lipids render them interesting for oral drug delivery purposes. Archaeal lipids form liposomes spontaneously (archaeosomes) and may be incorporated in conventional liposomes (mixed vesicles). Both types of liposomes are promising to protect their drug cargo, such as therapeutic peptides, against the acidic environment of the stomach and proteolytic degradation in the intestine. They appear to withstand lipolytic enzymes and bile salts and may thus deliver orally administered therapeutic peptides to distant sections of the intestine or to the colon, where they may be absorbed, eventually by the help of absorption enhancers. Archaeal lipids and their semisynthetic derivatives may thus serve as biological source for the next generation oral drug delivery systems. The aim of this review is to present a systematic overview over existing literature on archaea carrying diether and tetraether lipids, lipid diversity, means of lipid extraction and purification, preparation and in vitro stability studies of archaeal lipid-based liposomal drug carriers and in vivo proof-of concepts studies.